Mapatoppo as a The Tradition of Using Attributes for Bugis Migrant Pilgrims - M. Junaid (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
This study aimed to determine the reasons for migrant Bugis pilgrims to carry out the mapatoppo ritual, the mapatoppo process and the impact of the mapatoppo on the lives of migrant Bugis pilgrims. This research is included in qualitative field research. The research setting is located in Tanjung Jabung Timur Regency, Jambi Province with a focus on Kuala Jambi Subdistrict, especially Tanjung Solok Village and Kampung Laut Village as the base for overseas Bugis people. The research subjects in this study were the village head and his staff as many as 2 people, 20 people for haji and hajjah of Bugis migrants and 2 people as topanrita (ulama / ustadz) of Bugis. The results of this study found three main conclusions: first, the pilgrims were interested in performing the mapatoppo ritual because they considered the mapatoppo ritual as a symbol for wearing the pilgrims attributes officially. In addition, they also consider the mapatoppo ritual as a means of dipalecceki barakka (the process of transferring barakka / blessings from anre gurutta or sheikhs). Second, the mapotoppo process for the male congregation begins with the way they sit in a half circle in front of their sheikh. Then they are summoned before the sheikh one by one. Then they were asked to intend and then paired with a white rimless fezlike cap and surubeng by the sheikh. They do this in turn until it's finished. Meanwhile, the mapotoppo process for women congregation begins with the way they sit in a half circle in front of the sheikh's wife. Then they were asked to intend and they were taught to use talulung. After finishing using the talulung, then put trispak on top of the talulung. Then they are dressed in kabbe (skipping clothes). Third, the impact felt by pilgrims who have carried out the mapatoppo ritual is that they always wear Hajj clothing on official occasions and in everyday life. In addition, they also enforced againts not to work for 40 days. They just rested at home while worshiping and waiting for the arrival of their family and neighbors